Management Of Skills Competency Tests (Ukk) In State Vocational High Schools - Indah Puji Rahayu; Slamet Lestari (Jurnal Penelitian Pendidikan IPA, 2025)
Vocational education aims to equip students with skills aligned with industry demands. Competency Certification (UKK) is a key assessment to evaluate students’ readiness in Vocational High Schools (SMK). This study examines the management of UKK in SMK Negeri across Malinau Regency, focusing on planning, execution, and evaluation. Using a qualitative multi-site approach, the research involves school stakeholders, 12th-grade students, and examiners as key informants. The findings indicate that UKK implementation follows a structured process supported by industry collaboration. Supervision adheres to national guidelines, though a standardized fraud reporting system is lacking. Key challenges include student delays and limited equipment, while resource optimization and long-term projects serve as supporting factors. The study highlights the need for infrastructure improvements and enhanced supervision to ensure graduates meet industry standards, ultimately strengthening the quality of vocational education and workforce readiness.